THE INFLUENCE OF WORKLOAD AND WORK STRESS ON EMPLOYEE PERFORMANCE AT PT ASURANSI JASA TANIA TBK - Nurcahyo Adimulyo; Rora Ustria Mala; Sudianto (PENANOMICS: International Journal of Economics, 2023)
The purpose of this research is to find outThe Influence of Workload and Work Stress on Employee Performance at Pt Asuransi Jasa Tania TbkIn 2021, the number of the Company's employees will be185 people. The following table below presents information regarding the composition of the Company's employees by gender, position and age. In 2021, the number of the Company's employees is 185 people. Based on research conducted at PT Asuransi Jasa Tania, Tbk Pekanbaru, it can be concluded that workload has an effect and is significant on the performance of employees of PT Asuransi Jasa Tania, Tbk, Work Stress has no effect and is not significant on employee performance at PT Asuransi Jasa Tania, Tbk. Workload and workload have a significant and significant effect on employee performance at PT Asuransi Jasa Tania, Tbk. These results explain that the dependent variable, namely performance (Y), can be explained by the independent variable, namely workload ( X1) and work stress (X2) with a value of 64